Implementation Simulation Application of Library Accreditation Assessment of Indramayu State Polytechnic - Ghozali, Ahmad Lubis; Fitriyanti, Siti Aulia (Universitas Pendidikan Indonesia, 2024)
A library is a place that contains a collection of library materials used for study purposes or for reading purposes only. However, there are some libraries that have not implemented an assessment system in their management. Therefore, it is necessary to have a system as a supporting material to meet the accreditation assessment standards that have been set. So, an application was made to assist in conducting an assessment at the Indramayu State Polytechnic Library using the Laravel framework and in its development using the waterfall method. With this application, it is hoped that it will be able to facilitate the library in conducting assessments to achieve assessments that are in accordance with predetermined standards. The focus of this application development is focused on the accreditation assessment simulation process in the library. The results of the tests that have been carried out are running well, this application has succeeded in meeting the expectations that have been set previously, namely with an average value of 83.3% of the questionnaire calculation results